Prinsip-prinsip Total Quality Management dalam Membangun Lembaga Pendidikan Berbasis Mutu - Brillianov, Virgi Syafiq Ghiyats; Suklani; Brillianov, Suklani (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to explore the application of Total Quality Management (TQM) principles in enhancing the quality and effectiveness of quality-based educational institutions. The research uses a literature review to collect and analyze relevant bibliographic data, focusing on TQM principles: customer focus, involvement of all organizational members, continuous improvement, data-driven decision making, process approach, and quality-supportive leadership. The findings indicate that the application of TQM principles significantly improves the quality of education and operational effectiveness of educational institutions. Customer focus, which involves students, parents, and other stakeholders, enhances student satisfaction and learning outcomes. The involvement of all organizational members, including principals, teachers, and staff, fosters a sustainable quality culture. Continuous improvement drives quality enhancement through consistent evaluation and innovation, while data-driven decision-making helps identify and address deficiencies effectively. The process approach ensures operational efficiency, and quality-supportive leadership creates a conducive environment for achieving high-quality standards. Overall, systematic application of TQM principles can result in significant improvements in the quality and effectiveness of educational institutions.